LEADERSHIP IN MOTION: TRANSFORMING THEORY INTO REAL-WORLD COMMUNICATION - Foster-Wallace, Elizabeth Anne (International Journal of Allied Research in Marketing and Management (IJARMM), 2023)
This research-based report explores the intricate relationship between leadership principles and effective communication within organizations. Leadership effectiveness is intrinsically linked to the adept practice of two-way communication. This study delves into organizational communication and leadership by examining sources and types of power, offering a comparative analysis of power theories. Furthermore, it scrutinizes diverse leadership styles and their impacts, highlighting three specific styles. Fiedler’s Contingency Theory receives comprehensive attention in this report. Techniques and strategies for enhancing organizational communication are presented alongside an exploration of four distinct communication patterns. The report aspires to furnish a range of viable options, serving as a foundational resource for improving both organizational communication and leadership